The Household Food Security Status of Food Assistance Programs and Food Security Initiatives - Ssekate, Alfred (Journal of Food Sciences, 2024)
Purpose: The general objective of the study was to investigate the household food security status of food assistance programs and food security initiatives. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to household food security status and food assistance programs. Preliminary empirical review revealed that food assistance programs, including SNAP, WIC, and school meal programs, played a critical role in improving food security among vulnerable populations. However, it emphasized the importance of adopting a holistic approach to address underlying causes of food insecurity, such as poverty and systemic inequalities. Community-based initiatives and efforts to strengthen local food systems were identified as promising complements to traditional food assistance programs. Targeted interventions tailored to the unique needs of different population groups were also deemed essential. Overall, the study highlighted the need for coordinated efforts from various stakeholders to build resilient and equitable food systems and ensure access to nutritious food for all. Unique Contribution to Theory, Practice and Policy: The Social Determinants of Health theory, Systems theory and Capability Approach may be used to anchor future studies on household food security. The study provided valuable recommendations that contributed to theory, practice, and policy in addressing food insecurity. It integrated theoretical frameworks such as the Social Determinants of Health (SDH) theory, highlighting the complex dynamics underlying food insecurity. Practically, it emphasized the importance of multi-sectoral approaches, community engagement, and participatory decision-making in program design and implementation. At the policy level, the study advocated for comprehensive strategies that prioritize food security as a fundamental human right, including strengthening and expanding existing food assistance programs, fostering collaboration among stakeholders, and promoting evidence-based policy reforms. Overall, the study advanced understanding and action on food security by addressing systemic drivers, promoting collaborative practices, and advocating for policy changes.